The Costs and Benefits of Combining Gaze and Hand Gestures for Remote Interaction - Zhang, Yanxia; Stellmach, Sophie; Sellen, Abigail; Blake, Andrew (2015 International Conference on Human-Computer Interaction, 2015)
Gaze has been proposed as an ideal modality for supporting remote target selection. We explored the potential of integrating gaze with hand gestures for remote interaction on a large display in terms of user experience and preference. We conducted a lab study to compare interaction in a photo-sorting task using gesture only, or the combination of gaze plus gesture. Results from the study show that a combination of gaze and gesture input can lead to significantly faster selection, reduced hand fatigue and increased ease of use compared to using only hand input. People largely preferred the combination of gaze for target selection and hand gestures for manipulation. However, gaze can cause particular kinds of errors and can induce a cost due to switching modalities.